Martin Butler, Masculinity, and the North American Sole Leather Tanning Industry, 1871-1889 - Stiles, Deborah (Labour/Le Travailleur, 1998)
This article explores mid-19th century masculinity, through examination of the writings and lived experience of New Brunswick tannery worker Martin Butler. What being a man meant, in this historical context, was rooted in the contingencies and determinants of the North American sole leather tanning industry, and can be located as well in the discourses Martin Butler constructed about his and other men's experiences. Rural, working-class men, it is argued, were, in part, the shapers of their own class-specific and rurally-contingent male identities, although the processes by which these identities were formulated and negotiated are neither easily catalogued nor tidily analyzed. Cette étude appréhende la masculinité au milieu du siècle dernier par le prisme des écrits et de la vie du tanneur Martin Butler. Dans ce contexte* le sens de la masculinité était fondé sur les contingences et les déterminants de l'industrie des tanneurs de cuir de chaussures. Les discours de Butler sur ses expériences et celles de ses compagnons témoignent aussi de la construction de la masculinité à son époque. Les ruraux et les hommes de la classe ouvrières, croit-on, forgeaient partiellement leur identité spécifique, quoiqu'il soit difficile de cataloguer et d'analyser rigoureusement les processus formateurs de ces identités.